Estudio de caso: Almacenamiento de yuca fresca - Wheatley, Christopher C.; Izquierdo, D. (International Center for Tropical Agriculture, 1991)
The application of the integrated cassava project model in Colombia, in the case of fresh cassava marketing, is discussed. The research carried out during the 1980s to develop a fresh cassava product more attuned to consumer needs (storable, high quality, price-competitive) is reviewed, covering product idea generation (product ideas, idea screening, technical trials, market and consumer characteristics) and progressing through the different stages such as concept testing, feasibility study, and pilot projects in Bucaramanga and Barranquilla (farmer study, market study, consumer survey, onfarm trials of the storage technology, consumer panel operation and results, initial commercial experiences). To date, the pilot projects in Bucaramanga and Barranquilla have shown that the storage technology developed at CIAT is technically viable when carried out by farmers. It is also economical and the product is attractive and acceptable to consumers. Other projects have been initiated in other regions of Colombia (Sucre, Cesar, Santander) and projects are underway in Paraquay and NE Brazil. However, the final objective of obtaining a significant market share for cassava in bags in any urban center has yet to be achieved. The optimal organizational structure for marketing this product has yet to be developed and there is a lack of financing to promote activities by the marketing enterprise alone. Experience is needed in novel nontechnology aspects of product development to ensure replicability of these projects in other countries of Latin America and elsewhere. (CIAT)